Perception of Boredom in Leisure: Relationship with Internet Addiction and Perceived Social Competence - Feyza Meryem KARA; Bülent GÜRBÜZ (ümit doğan üstün, 2022)
This study aimed to examine the university students' perception of boredom in leisure, internet addiction and perceived social competence level with regard to some variables, and to test the relationship between these variables. "Leisure Boredom Scale (LBS), "Young Internet Addiction Test-Short Form" (YIAT-SF), and Perceived Social Competence Scale (PSCS) were applied to totally 430 (217 female and 213 male) university students selected by convenience sampling method. For the analysis of the data, t-test, MANOVA, ANOVA and simple correlation tests were used. Results indicated that the gender were significant only in "satisfaction" subscales of "LBS" in favour of women participants. MANOVA results indicated that main effect of regularly physical activity participation on "LBS", "PSCS" and "YIAT-SF" scores of participants. Further, there were statistically significant correlation between "LBS" and "YIAT-SF" and "PSCS" mean scores. As a result, it can be said that women participants manage their leisure or are aware of the psychological rewards of their leisure. However, regular physical activity participation is thought to provide low perception of boredom, high communication skills, sociability and online exploration behavior.